Solusi Alternatif Pada Bilangan Tiga Digit Kuadrat - Anzali, Wahyu Rifqi; Malasari, Putri Nur (Universitas Muhammadiyah Palembang, 2023)
Some of the mistakes made by students when working on math problems in square numbers included misapplied material concepts and not being careful in the calculation process which resulted in wrong final results. This study aims to provide alternative solutions in calculating square numbers. In addition, this research required an understanding of previously studied mathematical concepts. By used the literature study method, namely the method of collected data by understood and studied theories from various literature related to research. The results of the study obtained an alternative formulation of three- digit square numbers. Let's say ABC is any squared of any three-digit number. Then by multiplyied the usual stacked, we got the result that ABC²= A²2AB2AC+B²2ABC² regreded the five positions that are underlined, the operations started from the last and last order to the front. If the position operation results in a number of more than one digit, then the number with the last digit is used in that position, while the remaining digits are added with the position operation in front of it. Until the position operation ends at the forefront. As a result of applied this method requires understood the concept of the operation and memorization in applied the method